FROZEN STORAGE OF PORCINE ZYGOTE MEDIUM 3 FOR IN VITRO CULTURE OF CLONED PORCINE EMBRYOS - Zubing Caoa; Ronghua Wua; Dandan Song; Fei Han; Xia Li; Pengfei Zhang; Xiaorong Zhang; Yunhai Zhang (Journal of Animal and Plant Sciences, 2014)
`Frozen storage, in vitro culture, porcine embryo, pre-implantation development, PZM3
Keywords: Frozen storage; in vitro culture; porcine embryo; pre-implantation development; PZM3